PENINGKATAN HASIL BELAJAR MELALUI METODE EXAMPLES NON EXAMPLES PADA MATERI GEREJA SEBAGAI PERSEKUTUAN YANG TERBUKA KELAS XI NKPI DI SMK NEGERI 1 LAMALERA - Yakobus Belo Tobi; Veronika Buak (JIP: Jurnal Ilmu Pendidikan, 2026)
This study aims to determine how learning outcomes can be improved through the examples-nonexamples method in the subject of "The Church as an Open Fellowship" for class XI NKPI at SMK Negeri 1 Lamalera. This study is a Classroom Action Research (CAR) consisting of action planning, action implementation, observation, and reflection. This research was conducted in two cycles. The subjects in this study were 12 students. Data collection techniques in this study were observation and documentation. Data analysis in this study was descriptive analysis. The results of this study state that by using the lecture method on the subject of "The Church as an Open Fellowship", the category of students who achieved the Minimum Competency (KKM) was 25% and 75% did not. However, by applying the examples-nonexamples method to the subject of "The Church as an Open Fellowship", the student's completion score increased to 100%. Thus, learning outcomes on the subject of "The Church as an Open Fellowship" for class XI NKPI improved by applying the examples-nonexamples method.